SXR Measurements in INTI PF Operated in Neon to Identify Typical (Normal N) Profile for Shots with Good Yield - Saw, Sor Heoh; Rawat, Rajdeep S.; Lee, Paul; Talebitaher, Alireza; Abdou, Ali. E; Chong, Perk Lin; Roy, Federico; Ali, Jalil; Lee, Sing (IEEE, 2013)
The six-phase Lee model code was developed to compute the anomalous resistance phase (RAN) following the pinch phase in a plasma focus (PF) discharge. One important method to check such modeling is to look at the soft X-ray (SXR) emission time profile and to correlate this to the PF dynamics. A two-channel filtered SXR spectrometer coupled with an Excel-based analytical template was recently developed to speed up the correlation process. Using this system, we have determined that the neon PF typically operates in a normal (N) mode in which it emits characteristic He-like H-like neon line SXR (in a photon energy window of 900–1550 eV) reproducibly and efficiently. The characteristic neon line SXR pulse straddles the pinch duration starting strongly 10 ns before the start of the pinch, then diminishes through the 10-ns pinch and tails off into the subsequent RAN1 phase. We present the correlated time profiles of shots operating in the efficient N mode as well as, for comparison, poor shots, which are distinctly different in SXR time profiles. The profiles indicate the difference in dynamics of normal and poor shots. Statistics are presented as well as comparison of the yields from the numerical experiments and measurements. In the series that were studied the proportion of N-mode operation ranges from 70% in one series to 80% in another series over pressure range 1–4 torr. At 2 torr, it was found that 90% recorded the normal N profile. The results reinforce the view that while the Lee Model code incorporates the correct physics in its sequence of phases, refinement is needed to extend the radiative phase to the period before the pinch.